Bosna i Hercegovina - Kursar, Vjeran (2013)
The author analyzes political, social and demographic changes in Ottoman Bosnia and Herzegovina following the devastating war of 1683-1699. Despite turmoils of the first half of the 18th century, the situation improved in general in the second half of the century. After the brief evaluation of the position of all four confessional communities in the region - Muslims, Catholics, Orthodox Christian and Jews - the focus of the study shifts to Catholic community and the position of the Catholic Church in Bosnia and Herzegovina and Franciscans as its representatives.
Projekt MZOS
HRV